2018
DOI: 10.1016/j.celrep.2018.04.083
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1 Modulates Axonal Transport by Regulating α-Tubulin Acetyltransferase 1 Stability

Abstract: The protein p27 plays roles that extend beyond cell-cycle regulation during cerebral cortex development, such as the regulation of neuronal migration and neurite branching via signaling pathways that converge on the actin and microtubule cytoskeletons. Microtubule-dependent transport is essential for the maturation of neurons and the establishment of neuronal connectivity though synapse formation and maintenance. Here, we show that p27 controls the transport of vesicles and organelles along the axon of mice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 38 publications
(69 reference statements)
6
57
0
Order By: Relevance
“…Our recent data in mouse and human cancer cells support this hypothesis and suggest that p27 C-terminus, impacting on MT-dynamics via stathmin, can also regulate vesicle recycling, Ras signaling and, eventually, cell cycle entry and proliferation [17, 19, 33]. Similarly, the new work of Nguyen et al support the evidence that p27-mediated MT-acetylation, via α-TAT1 regulation, is necessary for vesicle transport along axons, in neurons [12]. Moreover, it is possible that the lack of p27 C-terminus could lead to a decreased protein stability, as recently shown, for instance, in the case of T197A knock-in mice that display most of the phenotypes described in p27 null animals [36].…”
Section: Main Textmentioning
confidence: 84%
See 2 more Smart Citations
“…Our recent data in mouse and human cancer cells support this hypothesis and suggest that p27 C-terminus, impacting on MT-dynamics via stathmin, can also regulate vesicle recycling, Ras signaling and, eventually, cell cycle entry and proliferation [17, 19, 33]. Similarly, the new work of Nguyen et al support the evidence that p27-mediated MT-acetylation, via α-TAT1 regulation, is necessary for vesicle transport along axons, in neurons [12]. Moreover, it is possible that the lack of p27 C-terminus could lead to a decreased protein stability, as recently shown, for instance, in the case of T197A knock-in mice that display most of the phenotypes described in p27 null animals [36].…”
Section: Main Textmentioning
confidence: 84%
“…Nguyen et al have recently observed that, in murine cortical neurons, p27 is located in multiple cytoplasmic compartments, including both dendrites and axons [12]. Projections from p27 knock out (p27 KO ) neurons displayed a reduced instantaneous and average transport velocity compared to wild-type (p27 WT ) controls.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Nguyen group also discovered, in mice cortical neurons, the involvement of p27 in the stabilization of alpha-tubulin acetyl transferase 1 (alpha-TAT1), the principal enzyme involved in MT post-translational modifications [ 73 ], adding important pieces of information to the comprehension of p27′s activity on MT cytoskeleton dynamics in vesicle trafficking and neuron migration. In addition, the cytoplasmic CDKI is involved in the enhancement of epithelial–mesenchymal transition, a well-known pro-carcinogenic process, by inducing Twist1 upregulation via the activation of STAT3 [ 74 ].…”
Section: P27 and P57 Proteins’ Major Features Properties And Funmentioning
confidence: 99%
“…Recently, Nguyen group also discovered in mice cortical neurons the involvement of p27 in the stabilization of alpha-tubulin acetyl transferase 1 (alpha-TAT1), the principal enzyme involved in MT post-translational modifications [73], adding important pieces of information to the comprehension of p27 activity on MT cytoskeleton dynamics in vesicles trafficking and neuron migration. In addition, the cytoplasmic CDKI is involved in the enhancement of epithelial-mesenchymal transition, a well-known pro-carcinogenetic process, by inducing Twist1 up-regulation via activation of STAT3 [74].…”
Section: P27: a Key Ambiguous Protein With Multiple Contrasting Rolesmentioning
confidence: 99%